STRATEGI PENGEMBANGAN WISATA SPIRITUAL PURA DALEM BALINGKANG DI DESA PINGGAN KECAMATAN KINTAMANI - Ni Wayan Ari Sudiartini; Ni Made Ana SastraDewi (Forum Manajemen, 2019)
Tourism is a variety of tourism activities and is supported by a variety of facilities and services provided by the community, entrepreneurs, central government and local governments. The development of Bali tourism has expanded to the corners of the village. In this study aims to determine the strategy of tourism development, especially spiritual tourism. The location of this research is in the suburb village of Kintamani district, Bangli Regency. This study uses qualitative research with descriptive methods and with a SWOT approach to discuss the contents. Data collection techniques by means of interviews, observation and documentation. The informants in this study were six people, namely the Sub-district Bendesa Adat, Jro Mangku Pura Dalem Balingkang, Prajuru Adat Pinggan, one of the rural village communities, one of the visitors to Pura Dalem Balingkang and a travel driver who drove passengers at Pura Dalem Balingkang. The results of this study indicate the spiritual tourism potential of Dalem Balingkang Temple in the form of temples, wantilan for staging ballet and gamelan, daily worship (Mebanten), religious ceremonies, and religious lectures (Darmawacana). The strategy used to develop spiritual tourism in Dalem Balingkang Temple is generally an improvement in aspects of accessibility, widening parking area, making tourism management bodies, and adding IT facilities and infrastructure, as well as training and community development.